Pengaruh Penerapan Sistem E-Filing, Pemahaman Perpajakan, Kesadaran Wajib Pajak, Sanksi Perpajakan, Pemahaman Internet, dan Kualitas Pelayanan terhadap Kepatuhan Wajib Pajak Orang Pribadi - Lucia Noviyanti; Meiriska Febrianti (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
This study aims to obtain empirical evidence and to determine the effect of the application of e-fiiling system, understanding taxation, awareness of taxpayers, taxable sanctions, internet understanding and quality of services on individual taxpayer compliance who registered in KPP Bekasi Region. This study uses primary data by distributing questionnaires via Google Form to individual taxpayers who registered in KPP Bekasi Region. The number of samples are 95 respondents. This research uses purposive sampling method. The method for the data analysis in this research is multiple linear regression processed by statistical tests. The results of this study indicate that the application of e-fiiling system, taxable sanctions, quality of services has an effect on individual taxpayer compliance, while understanding taxation, awareness of taxpayers, and internet understanding have no effect on individual taxpayer compliance.